Relation of Sufis with Hadith and Hadith Sciences - GÖKÇE, Ferhat (Scientific Journal of Faculty of Theology, 2018)
Approaches of Sufis in general terms to science, hadiths and hadith Science formed according to the understanding of irfan and ma'rifet both in terms of practical and theoretical. Therefore, It is necessary to determine how the Sufis have a perspective of the hadiths and hadith sciences that are regarded as one of the evident (zahir) sciences in the Sufi tradition. In particular, the irfani criteria that Hakim at Tirmizi (d. 285/898) revealed in evaluating the hadith texts to define maruf and munkar hadiths, The views of Abu Talib al-Makkî (d. 386/996) on ilm aljarh va ta’dil, weak hadiths and ra’y, Gazzâlî’s (d. 505/1111) evaluations of the hadiths in terms of irfan and ma'rifet represents the sûfî approach to hadith sciences. Abu Nasr Serrâc et-Tûsî (d. 378/988) put forward a different approach within the Sufis. et-Tûsî stated that the technical information about the chain (sanad) of the hadiths and hadith sciences must be left to the muhaddiths. In this article we will try to discuss the relation of the Sufis with the hadith and hadith sciences in the framework of the opinions of these authors.